Towards understanding the mode of action of the cytotoxic triosmium carbonyl cluster Os₃(CO)₁₀(NCCH₃)₂ : Its reactivity with amino acids and oligopeptides - Lee J.J.Y. (2021)
The reactions of the triosmium carbonyl cluster Os₃(CO)₁₀(NCCH₃)₂ (1) with a number of protected amino acids, tri- and pentapeptides were examined. The results show that reaction with the side chains follow the order: -SH > -COOH > -CONH₂, and there is a slight preference for the longer side chain of glutamic acid over aspartic acid. The trends observed are retained under physiological conditions and in the peptides.